2023
DOI: 10.1111/srt.13424
|View full text |Cite
|
Sign up to set email alerts
|

Role of macrophage scavenger receptor 1 in the progression of dyslipidemia in acne vulgaris patients

Abstract: BackgroundMacrophage scavenger receptor 1 gene (MSR1), is responsible for producing macrophage scavenger receptors. MSR1 is primarily located on the surfaces of various macrophage types and is known to exert a range of effects on the human body. These effects include influencing innate and adaptive immunological reactions, as well as contributing to the development of conditions such as atherosclerosis, dyslipidemia, liver and lung disease, and cancer. The unregulated assimilation of lipoproteins by MSR1 leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The linkage disequilibrium between rs433235 A > G and IVS5.59 C > A has been identified. Furthermore, there seems to be a strong linkage disequilibrium between rs3747531 C > G and rs433235 A > G. 12 …”
Section: Discussionmentioning
confidence: 99%
“…The linkage disequilibrium between rs433235 A > G and IVS5.59 C > A has been identified. Furthermore, there seems to be a strong linkage disequilibrium between rs3747531 C > G and rs433235 A > G. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Macrophage scavenger receptor 1 (MSR1) facilitates the incorporation and breakdown of modified LDL, leading to intracellular cholesterol accumulation and influencing macrophage functionality (33). AbdElneam et al found that of the four common haplotypes of the MSR1 gene, the most common haplotypes in patients with AV are TCAC and CAGG, whereas the most common haplotypes in healthy populations are TAAC and CCAC (34). Additionally, they observed a linkage disequilibrium in the MSR1 gene, indicating that genetic elements might significantly influence the development of AV by altering macrophage-mediated lipid regulation.…”
Section: Macrophages and Lipid Metabolism Regulationmentioning
confidence: 99%
“…14 In our population, several studies have been conducted to understand the relationship between genetic factors and dermatological conditions. [15][16][17][18][19][20][21][22][23][24] However, according to our knowledge, no study tries to determine the mechanisms by which miRNAs contribute to AA.…”
Section: Introductionmentioning
confidence: 99%